Programas de transferencias condicionadas : balance de la experiencia reciente en América Latina y El Caribe - Cecchini, Simone (UN CEPAL SantiagoCL, 2011)
Seeks to identify the role of conditional transfer programmes, one of the main tools to combat human poverty that has been implemented during the last 15 years in the region, and whose attention and replication have spread beyond its borders. Seeks to transform and stop the transmission of intergenerational poverty by developing human capabilities in the most vulnerable families. Delivers monetary and nonmonetary resources to families in povety or extreme poverty who have minor children, on condition that they comply with certain agreements associated with the improvement of their capabilities.\n \n \n